PENGARUH EDUKASI GIZI DENGAN MEDIA PERMAINAN KARTU DAN VIDEO ANIMASI TERHADAP PENGETAHUAN KONSUMSI BUAH DAN SAYUR PADA ANAK USIA SEKOLAH - Gendis Fathia Fajarina (2023)
Based on the results of the 2018 Riskesdas report, approximately 95.5% of the Indonesian population has insufficient consumption of vegetables/fruits. The impact of inadequate fruit and vegetable consumption can lead to several nutritional problems, such as obesity in schoolchildren and digestive disorders. One of the efforts that can be made to provide information related to fruits and vegetables is through educational interventions. The purpose of this research is to determine the influence of nutrition education using card games and animated videos on the knowledge of fruits and vegetables among school-aged children at Balekambang 01 Pagi Elementary School. The research design used was a quasi-experimental design with a pre-post test group design involving 124 students from grades III, IV, and V selected through stratified random sampling technique. There were differences in the pre-post test knowledge of the respondents regarding nutrition education using card game media (p = 0.000) and animated video media (p = 0.000). There was no significant difference in the knowledge improvement between the two media, as indicated by a p-value of 0.221 (p-value > 0.05). Conclusion of this research is there is an influence of nutrition education using card games and animated videos on the knowledge of fruits and vegetables among students at Balekambang 01 Morning Elementary School.